Polymerase activity of hybrid ribonucleoprotein complexes generated from reassortment between 2009 pandemic H1N1 and seasonal H3N2 influenza A viruses - Lam Wai Y; Ngai Karry LK; Chan Paul KS (Virology Journal, 2011)
Abstract Background A novel influenza virus (2009 pdmH1N1) was identified in early 2009 and progressed to a pandemic in mid-2009. This study compared the polymerase activity of recombinant viral ribonucleoprotein (vRNP) complexes derived from 2009 pdmH1N1 and the co-circulating seasonal H3N2, and their possible reassortants. Results The 2009 pdmH1N1 vRNP showed a lower level of polymerase activity at 33°C compared to 37°C, a property remenisence of avian viruses. The 2009 pdmH1N1 vRNP was found to be more cold-sensitive than the WSN or H3N2 vRNP. Substituion of 2009 pdmH1N1 vRNP with H3N2-derived-subunits, and vice versa, still retained a substantial level of polymerase activity, which is probably compartable with survival. When the 2009 pdmH1N1 vRNP was substituted with H3N2 PA, a significant increase in activity was observed; whereas when H3N2 vRNP was substituted with 2009 pdmH1N1 PA, a significant decrease in activity occurred. Although, the polymerase basic protein 2 (PB2) of 2009 pdmH1N1 was originated from an avian virus, substitution of this subunit with H3N2 PB2 did not change its polymerase activity in human cells. Conclusions In conclusion, our data suggest that hybrid vRNPs resulted from reassortment between 2009 pdmH1N1 and H3N2 viruses could still retain a substantial level of polymerase activity. Substituion of the subunit PA confers the most prominent effect on polymerase activity. Further studies to explore the determinants for polymerase activity of influenza viruses in associate with other factors that limit host specificity are warrant.